Correlational analysis of pollutant emission intensity in various conditions of operation of the automotive internal combustion engine - Chłopek, Zdzisław; Biedrzycki, Jacek; Lasocki, Jakub; Wójcik, Piotr (Transport, 2019)
The aim of this article was to analyse the correlation of emission intensity of carbon monoxide, hydrocarbons, nitrogen oxides, and carbon dioxide in various conditions of operation of the automotive internal combustion engine. The operational properties of the engine were investigated on chassis dynamometer in driving test cycles simulating various real-world conditions of the vehicle drive: street congestions, urban traffic without congestions, extra-urban traffic, and high-speed traffic. The correlational dependence of the pollutant emission intensity on the non-negative effective power of the engine and the correlational interdependence between the emission intensity of individual pollutants were investigated. The coefficients of Pearson’s linear correlation, Spearman’s rank correlation, Kruskal’s gamma correlation, and Kendall’s tau correlation were calculated. It was found that the emission intensity of pollutants in the driving test cycles strongly depends on the dynamic states of operation of the engine. The time histories of the emission intensity of pollutants were strongly correlated with the non-negative effective power of the engine. There were only a few cases where this correlation can be assessed as weak. The time histories of the emission intensity of individual pollutants were also strongly correlated with each other, with only a few exemptions.